“Nothing works without the doctor:” Physicians’ perception of clinical decision-making and artificial intelligence - Samhammer, David; Roller, Roland; Hummel, Patrik; Osmanodja, Bilgin; Burchardt, Aljoscha; Mayrdorfer, Manuel; Duettmann, Wiebke; Dabrock, Peter (Frontiers in Medicine, 2022)
Artificial intelligence driven decision support systems (AI-DSS) have the potential to help physicians analyze data and facilitate the search for a correct diagnosis or suitable intervention. The potential of such systems is often emphasized. However, implementation in clinical practice deserves continuous attention. This article aims to shed light on the needs and challenges arising from the use of AI-DSS from physicians’ perspectives. The basis for this study is a qualitative content analysis of expert interviews with experienced nephrologists after testing an AI-DSS in a straightforward usage scenario. The results provide insights on the basics of clinical decision-making, expected challenges when using AI-DSS as well as a reflection on the test run. While we can confirm the somewhat expectable demand for better explainability and control, other insights highlight the need to uphold classical strengths of the medical profession when using AI-DSS as well as the importance of broadening the view of AI-related challenges to the clinical environment, especially during treatment. Thus, our results stress the necessity for adjusting AI-DSS to shared decision-making. We conclude that explainability must be context-specific while fostering meaningful interaction with the systems available.